THE DEVELOPMENT MODEL OF ASSESSMENT WRITING BASED ON AUTHENTIC - Masrul Masrul (Journal of English Language and Education, 2017)
The destination of the research is to pattern a model of English learning assessment writing based on authentic for teacher and students of Senior High School English. Within few decades, the assessments of English learning process and learning outcomes for some aspects are isolated. The guides of English learning ways are teachers performance, students behavior toward English learning, and English learning amenities. Meanwhile in English learning outcomes the indicators are focused on writing. The result of isolating the learning process and outcomes are the students English writing based on authentic mitigated. The research design used is Research and Development (R&D). In this pattern, the development model and its setting are ADDIE (Analysis, Design, Develop, Implement and Evaluate). The products testing are carried out at Grade XI Natural Science of Senior High School in Bangkinang Town. The instruments of the research are observation, tests and questionnaires. The experts of assessments, methodology and English education test the validity, practicality and effectiveness of the model of English learning assessment writing based on authentic. The research finding indicates that the assessments of English learning process and learning outcomes affect to the students English writing based on authentic. The students English mastery is better when these two processes, learning process and learning outcomes are integrated. In conclusion, the assessment of English learning process and English learning outcomes must be comprehensively integrated. This indicates the importance of assessing English learning holistically